Management of patients with rare adult solid cancers: objectives and evaluation of European reference networks (ERN) EURACAN :health policy - Blay, Jean-Yves; Casali, Paolo; Ray-Coquard, Isabelle; Seckl, Michael J.; Gietema, Jourik; de Herder, Wouter W.; Caplin, Martyn; Klümpen, Heinz-Josef; Glehen, Olivier; Wyrwicz, Lucjan; Peeters, Robin; Licitra, Lisa; et al. (The lancet. Regional health, 2024)
About 500,000 patients with rare adult solid cancers (RASC) are diagnosed yearly in Europe. Delays and unequal quality of management impact negatively their survival. Since 2017, European reference networks (ERN) aim to improve the quality of care of patients with rare disease. The steering committee of EURACAN, including physicians, researchers and patients review here the previous actions, present objectives of the ERN EURACAN dedicated to RASC. EURACAN promoted management in reference centres, and equal implementation of excellence and innovation in Europe and developed 22 clinical practice guidelines (CPGs). Additionally, fourteen information brochures translated in 24 EU languages were developed in collaboration with patient advocacy groups (ePAGs) and seventeen training session were organized. Nevertheless, connections to national networks in the 26 participating countries (106 centres), simplification of cross-border healthcare, international multidisciplinary tumour boards, registries and monitoring of the quality of care are still required. In this Health Policy, evaluation criteria of the performances of the network and of health care providers are proposed.